Detection and quantitation of immunogenic epitopes related to celiac disease in historical and modern hard red spring wheat cultivars. (30th October 2018) - Malalgoda, Maneka; Meinhardt, Steven W.; Simsek, Senay
Highlights: Celiac-disease-initiating peptides were detected in both historical and modern wheat. The amount of glia-α9 and total α-gliadin varied randomly across the cultivars. Modern wheat is not higher in celiac antigenicity compared to historical wheat. Abstract: Celiac disease (CD) develops in genetically susceptible individuals as a result of ingesting gluten-forming proteins found in cereals, such as wheat ( Triticum aestivum L.), rye ( Secale cereale L.) and barley ( Hordeum sativum L.). There are claims that breeding practices have changed wheat protein chemistry over the years and this has resulted in modern wheat being more antigenic in terms of CD as opposed to historical wheat. The aim of this study was to detect and quantify celiac-disease-initiating peptides of α-gliadin proteins in historical and modern spring wheat cultivars. The results indicate that immunogenic epitopes are detected in both historical and modern spring wheat cultivars irrespective of release year. Quantitation indicated that the amount of immunogenic epitopes glia-α9 (PFPQPQLPY) and glia-α20 (FRPQQPYPQ), and total α-gliadin varied randomly across the cultivars that were analyzed, suggesting there is no association between cultivar release year and amounts of immunogenic epitopes and α-gliadin.